High intensity proton beam dynamics simulation in the initial part of ADS LINAC - Dyubkov, V.S. (Вопросы атомной науки и техники, 2013)
One of the most important scientific and technical challenges is the design and development of a new type power reactor, which has a higher nuclear safety. At present several projects related to the so-called hybrid (subcritical) reactors, based on high power proton accelerators, are realized worldwide. Accelerator-driver, as a part of hybrid system (ADS), must meet a number of requirements, among which small losses of the accelerated particles. To fulfill this requirement, it is necessary to ensure small beam emittance at the injector output, exact alignment and work stability of all accelerator parts, a careful study of the beam halo formation and envelope control. On the basis of the developed beam envelope control method main parameters of the linear accelerator-driver initial part which provide high acceleration rate under small particle losses are chosen. Numerical simulation of self-consistent high intensity proton beam dynamics in the initial part of the accelerator-driver is performed.